Efektifitas Terapi Pijat Refleksi Kaki Terhadap Pengendalian Glukosa Darah Pada Penderita Diabetes Melitus - Mardiana Mardiana (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2021)
Introduction: Diabetes mellitus is a group of metabolic disorders characterized by damaged insulin secretion, insulin action, or both, resulting in an increase in blood glucose levels (hyperglycemia). The impact of chronic hyperglycemia and metabolic disorders with diabetes mellitus, which causes damage to tissues and organs such as the eyes, nerves, kidneys and blood vessel systems.Purpose: This literature study aims to analyze the effectiveness of foot reflexology therapy in controlling blood glucose in diabetic patients.Methods: the database in making this literature review is pubmed and google scholar. The articles found were in the 2015-2021 timeframe with full text and were selected according to the appropriate literature study topic.Results: Based on the results of literature search, 331 articles were found, and there were 5 articles that met the criteria regarding the effectiveness of foot reflexology therapy in controlling blood glucose in diabetic patients.Conclusion: The results of research from several articles in this literature review indicate that foot reflexology therapy is effective in controlling blood glucose in diabetic patients.Keywords: Blood Glucose, Diabetes, Massage Therapy, Foot Reflexology